Mysticism and Politics : A Critical Reading of Fī ẓilāl al- Qur'ān by Sayyid Quṭb (1906-1966) - Carré, Olivier (Brill Book Archive Part 1, ISBN: 9789004472495., 2003)
This volume deals with Sayyid Quṭb's commentary, compared to 'Abduh's and Riḍā's 'Tafsīr al-Manār', discussing his method of reading the Qur'ān, elements of his dogmatic theology, of his faith and spirituality and of the Muslim practices.The book then evaluates his doctrine concerning Judaism and Christianity, the status of their followers in the ideal Islamic society to be reinstated, Muslim family and Islamic emancipation of women. It evaluates which Islamic State will be able to accomplish and lead this Qur'ānic society, and what will be its 'dynamic Law' and the new economic order and social justice. The book finally looks at the essential role the permanent war-for-God should have in the face of new worldwide anti-Islamic paganism, and it concludes with extremism (of Quṭb and, more, of the 'Quṭbists') and with the promising muslim thinking in resistance to it. The large Selection of texts of 'Fī ẓilāl...', translated by W. Shepard, is very valuable.